In Vitro Cultivation of Porcine Chondrocytes on Fully Surface-Modified Polycaprolactone Scaffold: Static versus Dynamic Cultures - Pakkanun Kaewkong (Science Faculty of Chiang Mai University, 2019)
Tissue engineering has been anticipated to be a promising therapeutic approach for cartilage damage. Hence, the development of a suitable scaffold for reconstruction of neocartilage is one of the key issues. In this study, polycaprolactone (PCL) was used as a scaffold in two different cell culture processes: static and dynamic cultures. The former was simply conducted in a cell culture plate, while the latter was performed in an in-house-built flow perfusion bioreactor at a flow rate of 0.1 ml/min. In the preparation of the fully surface-modified PCL scaffold, PCL pellets were first alkaline hydrolyzed prior to fabrication by a high pressure supercritical CO2 technique. This resulted in the hydrolyzed PCL (HPCL) scaffold with pore sizes ranging from 150 to 250 mm, whose surface was further subjected to an oxygen plasma treatment. The surface morphology, wettability, and chemical composition of the resulting scaffold were analyzed by scanning electron microscopy (SEM), water contact angle measurement, and X-ray photoelectron spectroscopy (XPS), respectively. It was found that the surface roughness and hydrophilicity of the PCL scaffold were drastically enhanced after the treatments. The proliferation of porcine chondrocytes cultured on the fully surface-modified PCL scaffold was found not to be different under both static and dynamic culture environments. However, the dynamic culture could promote the cells cultivated on the scaffold to function more effectively with a higher production and accumulation of extracellular matrix and a greater secretion of two important cartilage specific components, type II collagen and aggrecan. The total GAG content produced by the cells cultured in the bioreactor was about 95 mg/scaffold, while that produced in the well plate was only about 28 mg/scaffold. In addition, it was noted that the fully surface-modified PCL scaffold facilitated the infiltration of the cells down through the scaffold. The use of the suitably surface-modified PCL scaffold, together with the application of a flow perfusion bioreactor, potentiated the in vitro generation of cartilaginous extracellular matrix components.